Profil Penyesuaian Sosial Siswa Berdasarkan Gender Di Smk Pgri Jatiwangi - Roslina, Devi; Asiyah, Dewi; Mahmudah, Mahmudah (Jurnal Eksplorasi Bimbingan dan Konseling, 2023)
This study is a descriptive study with a survey method that aims to determine the profile of students' social adjustment based on gender at SMK PGRI Jatiwangi in the 2020/2021 academic year. This study uses library research so that the existing data is a detailed collection of various literature studies related to the theme of social adjustment in various fields and problems and their solutions. It was concluded that the problem of social adjustment certainly has a solution, namely how a guidance and counseling teacher provides treatment that does not make students bored while experiencing various problems, especially in the environment of students who experience mental changes in high school / vocational schools. The results of the thesis research entitled Profile of Students' Social Adjustment Based on Gender at SMK PGRI Jatiwangi obtained the results of handling and how BK teachers deal with existing problems, especially in the field of social adjustment, both for male and female genders.